2020
DOI: 10.1186/s40854-020-00176-3
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin pricing: impact of attractiveness variables

Abstract: The research seeks to contribute to Bitcoin pricing analysis based on the dynamics between variables of attractiveness and the value of the digital currency. Using the error correction model, the relationship between the price of the virtual currency, Bitcoin, and the number of Google searches that used the terms bitcoin, bitcoin crash and crisis between December 2012 and February 2018 is analyzed. The study also applied the same analysis to prices of Bitcoin denominated in different sovereign currencies trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…(2018) also find Google searches as a significant factor in determining bitcoin prices. Hakim das Neves (2020) have similar findings, suggesting that the bitcoin price increase is significantly affected by the number of Google searches throughout the world. Hayes (2016) establishes a strong evidence toward energy consumption being a driver of bitcoin value.…”
Section: Literature Reviewsupporting
confidence: 54%
“…(2018) also find Google searches as a significant factor in determining bitcoin prices. Hakim das Neves (2020) have similar findings, suggesting that the bitcoin price increase is significantly affected by the number of Google searches throughout the world. Hayes (2016) establishes a strong evidence toward energy consumption being a driver of bitcoin value.…”
Section: Literature Reviewsupporting
confidence: 54%
“…Studies also found evidence of micro or macro fundamental factors that affect Bitcoin price. For example, Neves [42] suggested that investment attractiveness had a prominent role in Bitcoin price formation, while other researchers [3,34,43,44] argued the stock market, exchange rate, gold, oil, Economic Policy Uncertainty (EPU), and the Geopolitical Risk Index, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was suggested in [23] that fundamental factors such as real use in transactions and money supply affect the long-term price of Bitcoin, and investors' interest in cryptocurrency reinforces this phenomenon. In [24], Google search term queries were used on Bitcoin to reveal that global interest in Bitcoin precedes price increases; in contrast, prices fall when fear of market collapse increases. In [25], it was found that public interest and Bitcoin prices had a high correlation.…”
Section: Factors Affecting Changes In the Price Of Bitcoinmentioning
confidence: 99%